Case report: Dupilumab treatment improved type 2 disorders in a patient with IPEX syndrome diagnosis - Caruso, C.; Laterza, L.; Settanni, C. R.; Colantuono, S.; Di Mario, C.; Tolusso, B.; Castrì, F.; Gremese, E.; Scaldaferri, F.; Armuzzi, A.; De Simone, C.; Peris, K.; et al. (Frontiers in Immunology, 2023)
We described a case of IPEX syndrome successfully controlled with dupilumab, an anti-IL4 receptor alpha subunit inhibitor. IPEX syndrome is a rare and generally fatal genetic disorder characterized by immune dysregulation, polyendocrinopathy and enteropathy, mostly diagnosed in early childhood. . Nonetheless, cases reported in the last 20 years demonstrated that IPEX clinical spectrum encompasses more than the classical triad of early-onset intractable diarrhea, type 1 diabetes and eczema. Atypical cases of IPEX include patients with late-onset of symptoms, single-organ involvement, mild disease phenotypes or rare clinical features. A 21-year-old caucasian man presented with immune dysregulation (hypereosinophilia and elevated IgE), protein-losing enteropathy, polyendocrinopathy (thyroiditis, osteoporosis, delayed puberty), weight loss, eczema manifestations and celiac disease. IPEX syndrome was diagnosed because of the presence of a hemizygous mutation in FOXP3 gene (c.543C>T (p.S181S) in the exon 5). During the course of the disease, the patient developed erosive proctitis, pyoderma gangrenosum, and erythema nodosum. Symptoms improved only after enteral and parenteral corticosteroid therapy and the patient soon developed steroid-dependence. Notwithstanding various therapies including azathioprine, sirolimus, tacrolimus, adalimumab, vedolizumab, the patient failed to achieve a good control of symptoms without steroids. Almost exclusive enteral nutrition with a hypoallergenic, milk-protein free, amino acid-based food for special medical purposes. He continued to lose weight (BMI 14.5 kg/m2) with a consequent high limitation of physical activity and a progressive worsening of the quality of life. In consideration of the poor response to conventional immunosuppressants and the presence of type 2 inflammatory manifestations, treatment with dupilumab at an initial dose of 600 mg, followed by a maintenance dose of 300 mg every other week, according to atopic dermatitis labeled dose, was started and combined to oral budesonide 6 mg/day and 6-mercaptopurine 75 mg/day. The patient experienced a rapid improvement in bowel and skin symptoms, leading to a progressive tapering of steroids. By our knowledge, this is the first report of IPEX syndrome successfully treated by antiIL-4/IL-13 therapy. In this case dupilumab demonstrated to be an effective, safe and steroid-sparing option.